Inducible Knockout of the Cyclin-Dependent Kinase 5 Activator p35 Alters Hippocampal Spatial Coding and Neuronal Excitability - Kamiki, Eriko; Boehringer, Roman; Polygalov, Denis; Ohshima, Toshio; McHugh, Thomas J. (Frontiers in Cellular Neuroscience, 2018)
p35 is an activating co-factor of Cyclin-dependent kinase 5, a protein whose dysfunction has been implicated in a wide-range of neurological disorders including cognitive impairment and disease. Inducible deletion of the p35 gene in adult mice results in profound deficits in hippocampal-dependent spatial learning and synaptic physiology, however the impact of the loss of p35 function on hippocampal in vivo physiology and spatial coding remain unknown. Here we recorded CA1 pyramidal cell activity in freely behaving p35 cKO and control mice and found that place cells in the mutant mice have elevated firing rates and impaired spatial coding, accompanied by changes in the temporal organization of spiking both during exploration and rest. These data shed light on the role of p35 in maintaining cellular and network excitability and provide a physiological correlate of the spatial learning deficits in these mice.